An automatic jigsaw puzzle solver - Kosiba, D.A.; Devaux, P.M.; Balasubramanian, S.; Gandhi, T.L.; Kasturi, K. (Pattern Recognition, 1994 12th International Conference On. Vol. 1, 1994)
A computer vision system to automatically analyze and assemble an image of the pieces of a jigsaw puzzle is presented. The system, called Automatic Puzzle Solver (APS), derives a new set of features based on the shape and color characteristics of the puzzle pieces. A combination of the shape dependent features and color cues is used to match the puzzle pieces. Matching is performed using a modified iterative labeling procedure in order to reconstruct the original picture represented by the jigsaw puzzle. Algorithms for obtaining shape description and matching are explained with experimental results.